2022
DOI: 10.3390/ijms232012558
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots Modified Upconversion Nanoparticles for Photodynamic Therapy

Abstract: Photodynamic therapy (PDT), as a novel technique, has been extensively employed in cancer treatment by utilizing reactive oxygen species (ROS) to kill malignant cells. However, most photosensitizers (PSs) are short of ROS yield and affect the therapeutic effect of PDT. Thus, there is a substantial demand for the development of novel PSs for PDT to advance its clinical translation. In this study, we put forward a new strategy for PS synthesis via modifying graphene quantum dots (GQDs) on the surface of rare-ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This method provides a new paradigm with highly integrated functions that shows excellent prospects for PDT development. 73 …”
Section: Graphene and Graphene Derivatives In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…This method provides a new paradigm with highly integrated functions that shows excellent prospects for PDT development. 73 …”
Section: Graphene and Graphene Derivatives In Oncologymentioning
confidence: 99%
“…UCNPs@GQDs exhibited high biocompatibility and obvious concentration-dependent PDT efficiency, shedding light on nanomaterials-based PDT development. [ 73 ] BSArGO@ZIF-8 NSs HeLa and SCC25 c BSArGO@ZIF-8 NSs can promote cell apoptosis by initiating bim (a pro-apoptotic protein)-mediated mitochondrial apoptotic events, up-regulating PUMA/NOXA expression, and down-regulating the level of Bid/p53AIP1. Zn2+ excess triggers cellular dysfunction and mitochondria damage by activating the autophagy signaling pathways and disturbing the intracellular environmental homeostasis.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…The scalability, cost-effectiveness, and regulatory approval of GQDs synthesis and formulation must be addressed. Moreover, the integration of GQDs with other therapeutic modalities, such as chemotherapy or immunotherapy, should be explored to achieve synergistic effects and improve overall therapeutic outcomes [38,39].…”
Section: Current Trends In Discrimination Of Gqd-based Pdt/ptt Strate...mentioning
confidence: 99%
“…As Li et al stated, such functionalized GQDs show biocompatibility and concentration-dependent PDT efficiency. 334 It is also possible to use other lasers, like the one with micro-watt power (290 μW) 365 nm UV tube light, as Ahirwar et al reported. 315 Ahirwar et al also showed that GQDs and GOQDs both have strong absorbance in the UV region and ROS generation.…”
Section: Use Of Graphene-based Materials To Enhance Pdtmentioning
confidence: 99%